2005
DOI: 10.1002/cne.20832
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal cells of the rat basolateral amygdala: Synaptology and innervation by parvalbumin‐immunoreactive interneurons

Abstract: The generation of emotional responses by the basolateral amygdala is largely determined by the balance of excitatory and inhibitory inputs to its principal neurons, the pyramidal cells. The activity of these neurons is tightly controlled by GABAergic interneurons, especially a parvalbumin-positive (PV+) subpopulation that constitutes almost half of all interneurons in the basolateral amygdala. In the present semi-quantitative investigation we studied the incidence of synaptic inputs of PV+ axon terminals onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
226
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(242 citation statements)
references
References 93 publications
16
226
0
Order By: Relevance
“…Support for this proposed role for DF cells comes from their somatic innervation of principal neurons based on the rapid kinetics of the IPSCs they produce, and their depolarized spike threshold, which would tailor them to regulate excessive principal neuron output. Ultrastructural data showing that ϳ50% of somatic symmetrical synapses express parvalbumin (Muller et al, 2006) is also consistent with this proposal.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Support for this proposed role for DF cells comes from their somatic innervation of principal neurons based on the rapid kinetics of the IPSCs they produce, and their depolarized spike threshold, which would tailor them to regulate excessive principal neuron output. Ultrastructural data showing that ϳ50% of somatic symmetrical synapses express parvalbumin (Muller et al, 2006) is also consistent with this proposal.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, as with our AC cells, dendritic interneurons possess slower membrane time constants, exhibit spike frequency adaptation, and fire broader action potentials than their somatic counterparts (Beierlein et al, 2003;Jonas et al, 2004;Pouille and Scanziani, 2004). Furthermore, ultrastructural studies have shown that a substantial proportion (20ϳ28%) of PVϩ terminals in the cat (Smith et al, 1998) and rat (Muller et al, 2006) basal amygdala target principal neuron distal dendrites, suggesting a similar anatomical organization of the PVϩ synapses in the three species. It has also been estimated that up to 40% of calbindinexpressing interneurons in the rat basolateral nucleus, the majority of which are likely to also express parvalbumin, target distal principal neuron dendrites (Muller et al, 2003).…”
Section: Discussionsupporting
confidence: 67%
“…We suspect that the internal solution was not adequately perfused at the distal site of the thin dendrite, and insufficient exchange of intracellular solution perturbs the shift of the equilibrium potential, leaving it near the original value. This speculation is supported by reports on the presence of GABAergic synapses in distal dendrites in BLA pyramidal neurons (Muller et al, 2006(Muller et al, , 2007.…”
Section: Ntsr1 Regulates Amygdala Ltp T Amano Et Alsupporting
confidence: 65%
“…Chandelier synapses have also been described in the amygdala, and these terminals are known to express parvalbumin (Kemppainen and Pitkanen, 2000;McDonald and Betette, 2001;Muller et al, 2006). Because cortical AAC interneurons express parvalbumin (Howard et al, 2005), we tested whether interneurons that provide disynaptic excitation in the amygdala may also make chandelier synapses.…”
Section: Interneurons Evoke Feedback Glutamatergic Excitationmentioning
confidence: 99%